The Trios ‘del sigr Avondano’ in Dresden (Per Musi, 2018)
Dresden Public Library holds three trio sonatas attributted to ‘sgnr Avondano’, bearing the ID catalog Mus.2661-Q-1/2/3. This paper aims at finding aspects of authorship and dates, by means of collecting historical data. It discusses criteria that allow elucidate aesthetic and stylistic influences in the musical discourse of the period and provide insights for historically informed performances.